KUALITAS PELAYANAN PUBLIK - Talenta Udur Manalu (Universitas Riau, 2016)
Quality of Public Services. This study aims to determine the quality of public services and the factors that affect the quality of public services in outpatient installation Mental Hospital Tampan Pekanbaru. This study uses qualitative methods of collecting data obtained from observations of researchers in the field and in-depth interviews with informants research, namely: family outpatient registration clerk, medical records clerk, nurse clinics, general practitioners and specialists. Data analysis was carried out simultaneously with data collection from data collection, data reduction, data presentation and decision-making or data verification. Based on the results, the quality of public services in outpatient installation Psychiatric Hospital Tampan Pekanbaru as follows: Tangible; of the facility is still not optimal, Reliability; Hospital outpatient installation Tampan Pekanbaru soul has been providing services as promised are accurate and reliable, Responsiveness; lack of specialist doctor of psychological / psychiatric causes slow service in a specialist clinic so that patients wait long queues, Assurance; there is still reluctance clerk at outpatient installation in giving a shout out to the public visitors and Emphaty; efforts Tampan Pekanbaru Mental Hospital to determine the needs of customers or patients by providing a suggestion box.